Cultural chrono-categories from Mendoza and San Juan, Argentina - Aguilar, Humberto (2025)
This work involved the collection, systematization, and normalization of 93 archaeological period definitions used in the provinces of Mendoza and San Juan (Argentina), extracted from over 500 bibliographic sources. The data were published in the open gazetteer of the PeriodO Project and in the Digital Repository of the National University of Córdoba. Este trabajo consistió en el relevamiento, sistematización y normalización de 93 definiciones de periodos arqueológicos utilizados en las provincias de Mendoza y San Juan (Argentina), extraídas de más de 500 fuentes bibliográficas. Los datos fueron publicados en el gazetteer abierto del proyecto PeriodO y en el Repositorio Digital de la Universidad Nacional de Córdoba.